The molecular pathogenesis of head and neck cancer - Klein, Jonah D. (2010)
Head and neck cancer arises from a series of molecular alterations progressive from dysplasia to carcinoma in situ, and finally invasive carcinoma. Risk factors associated with head and neck cancer include tobacco, alcohol and viral infection. There are genetic alterations in pre-cancerous cells that contribute to transformation. The accumulation of these alterations facilitates tumor development. Additionally, the tumor microenvironment enables tumor progression. The cooperative effect of molecular alterations in the tumor cells and compensatory microenvironment changes enable tumors to invade and metastasize. This review focuses on the genes and molecules altered during the progression of head and neck cancer with an emphasis on the genetic, molecular and phenotypic changes during the pathogenesis of head and neck cancer. Therapeutic strategies that target key changes in the tumor cells and/or stromal cells in the tumor microenvironment are discussed.